When Hippo was hairy : and other tales from Africa - Greaves, Nick; Clement, Rod (New York : Barron's, 1988)
Thirty-six animal folktales from all parts of Africa, with factual information about each animal following the stories.
Includes bibliographical references (page [144])
Keywords: Tales -- Africa; Animals -- Folklore